Islamic Religious Education Curriculum Design for Junior High School Level - Edi Supardi; Nina Nursilah; Dicky Darmawan; Faiz Fahmi (UIN Sunan Gunung Djati Bandung, 2026)
The shift in the national education paradigm marked by the implementation of the Independent Curriculum demands the design of an Islamic Religious Education (PAI) curriculum that is in line with current developments, but remains rooted in Islamic values. At the Junior High School (SMP) level, PAI not only serves as a means of transmitting religious knowledge but also as a medium for the formation of students' character and spirituality. This study aims to examine and design an Islamic Religious Education (PAI) curriculum for junior high school level based on national regulations, Islamic education principles, and learning outcomes set out in the Independent Curriculum. This study uses a qualitative approach with a literature study method through the collection and analysis of various relevant literature. The results show that the design of the PAI curriculum must include main components such as Learning Outcomes (CP), Learning Objectives (TP), Learning Objective Flow (ATP), and Teaching Modules. Each component is designed integratively to create contextual, flexible learning that focuses on strengthening students' noble character. Overall, this study provides a theoretical contribution to the development of an operational curriculum for Islamic Religious Education at the junior high school level.